Sistem Pemantau dan Pengaman Hama Babi Hutan Berbasis IoT pada Lahan Ubi Kayu di Jantho Baru - Aceh Besar - Ramzi Adriman; Afdhal Afdhal; Munzir Umran; Dien Taufan Lessy; Syarizal Fonna (Universitas Syiah Kuala, 2025)
Wild boars pose a significant threat to cassava farmers in the Jantho Baru area, Aceh Besar district, as they can reduce agricultural productivity. The region's location in hilly terrain near a protected forest makes this challenge unavoidable. An initial assessment with farmer groups (partners) identified the need for a monitoring and protection system to manage wild boar infestations in cassava farms. The partner's land, situated 42 km from the Faculty of Engineering, Universitas Syiah Kuala, spans 5 hectares in a hilly area adjacent to the protected forest.To address this issue, an IoT-based technology solution is proposed for monitoring and safeguarding cassava farms. This system includes video cameras that allow farmers to remotely monitor their land via smartphones. Additionally, security measures such as electric fences and speaker outputs, controlled through an Android-based mobile application, are implemented. The system is powered by renewable solar energy through the use of solar panels. The application of this technology is expected to reduce crop losses caused by wild boars, ultimately improving farm productivity.